Numerical study of the static and dynamic characteristics of reinforced concrete cassette structures for high‐rise buildings. (11th December 2018) - Chen, Zhi‐Peng; Wu, Gang; Feng, De‐Cheng; Ma, Ke‐Jian
Summary: High‐rise buildings are extensively built in China, and the structure of these buildings is composed of different types of conventional system of which framed structures are more commonly employed. A new cassette structure with advantageous performance properties is proposed. Static and dynamic numerical simulations were applied to investigate the characteristics of this new structure. First, the components and other details are presented. A comparative analysis was conducted between the cassette structure and traditional structures using eight finite models with fiber elements in three different heights. A static pushover analysis and an incremental dynamic analysis were conducted based on 18 near‐ground motion records recommended by the Federal Emergency Management Agency. The seismic characteristics, deformation curve, interstory drift, roof displacement, and fragility curve are investigated. Based on the analysis of the models with three different heights and the variety of seismic records, the economic advantage and application of cassette structures for building industrialization are also discussed.